Teknologi Informasi Dalam Transformasi Penyiangan Koleksi: Dari Koleksi Tercetak Sampai Pada Koleksi Digital - Winoto, Yunus Winoto; Septian, Falih Ijlal; Shuhidan, Shamila Mohamed (Al-Ma mun Jurnal Kajian Kepustakawanan dan Informasi, 2025)
This study aims to examine how information technology changes the practice of weeding collections, identify the challenges faced in the transformation process, and formulate strategic solutions that can be implemented by libraries. The method used in this study uses a literature study, namely a research method carried out by collecting, analyzing, and interpreting information or data obtained from various written sources, such as books, scientific articles, research reports, journals, theses, dissertations, official documents, and other literature sources that are relevant to the topic being studied. Based on the results of the study, it shows that the application of information technology has brought significant changes in the weeding process, starting from collecting, evaluating to filtering digital collections. In addition, the transformation in weeding collections can increase efficiency, accuracy, and accountability in weeding decision making.